Joint resource allocation and relay selection via genetic algorithm in multi‐user decode‐and‐forward cooperative systems. Issue 2 (1st June 2014) - Fang, Wen‐Hsien; Chen, Chien‐Fu; Lang, Hung‐Sheng
Abstract : This study presents a joint consideration of the relay subset selection, bandwidth allocation and power distribution in multi‐user decode‐and‐forward cooperative networks. The upper bound for the optimisation problem considered is first determined by ignoring some constraints. Thereafter, a genetic algorithm (GA) is addressed to resolve the mixed‐integer non‐linear programming problem involved. To accommodate this joint consideration, each chromosome in the proposed GA is divided into an integer string for relay selection, and two real number strings for bandwidth allocation and power distribution. In addition, new crossover and mutation operations are employed for this new type of chromosomes. To alleviate the complexity overhead, a low‐complexity two‐stage implementation is also addressed. Conducted simulations show that both of the proposed GA and the two‐stage implementation can attain close performance as the upper bound and outperform some representative previous works. The two‐stage implementation is in particular appealing by exhibiting negligible performance degradation with reduced computations.